2020
DOI: 10.1177/0734242x20941088
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability indicators for municipal solid waste management: A case study of the Recife Metropolitan Region, Brazil

Abstract: Municipal solid waste (MSW) management in Brazil faces major challenges in order to meet the requirements proposed by the National Solid Waste Policy, which has been in force since 2010 and complicates decision-making, especially in small municipalities. In this context, sustainability indicators are important support tools that help in setting out performance actions for municipal sustainable development. The main objective of this article is to evaluate the four sustainability dimensions (social, environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…More time is needed, but these yield higher quality results [99][100][101][102]. Other data collection methods include the use of expert score sheets [83,103], reviews of local context and policies [87], assessments of environmental authority reports [104], the gathering of sustainability indicators from national information system databases, municipal or national agencies [104][105][106], and an examination of newspapers [107].…”
Section: Social Dimensionsmentioning
confidence: 99%
“…More time is needed, but these yield higher quality results [99][100][101][102]. Other data collection methods include the use of expert score sheets [83,103], reviews of local context and policies [87], assessments of environmental authority reports [104], the gathering of sustainability indicators from national information system databases, municipal or national agencies [104][105][106], and an examination of newspapers [107].…”
Section: Social Dimensionsmentioning
confidence: 99%
“…In a recent study, Juca et al (2020) used sustainability indicators for dealing with the waste management issues in northeastern Brazil. They considered four sustainability dimensions, that is, economic, social, legal, and environmental in their analysis.…”
Section: Indicators For Waste Managementmentioning
confidence: 99%
“…Fast urbanization has considerably augmented municipal solid waste (MSW)’s generation through the previous decades (Farahbakhsh and Forghani, 2019; Raviv et al, 2018; Stemn and Kumi-Boateng, 2019). For example, the MSW production has expanded to 1.3 B tons year −1 globally from 0.68 B tons year −1 10 years before, and it is expected to touch the 2.2 B tons year −1 mark by 2025 and 2.6 B tons year −1 by 2030 (Juca et al, 2020; Maalouf et al, 2020; World Bank, 2012). Recently, Muaaz-Us-Salam et al (2019) reported that total MSW production would possibly rise over 300% globally by 2100.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the waste management literature in Brazil is focused on MSW, reflecting the substantial challenges faced by municipalities in meeting the requirements outlined in the PNRS of 2010. For example, Rebehy et al [26] studied the variables that influence the recovery of solid waste and best practices of efficient municipalities in Brazil; Paes et al [25] focused on the main enablers of innovations in solid waste management in four municipalities and the respective actions between circular economy and climate change; Silva et al [27] investigated the potential of utilizing MSW as refuse-derived fuel and the respective energy and greenhouse gas emissions impacts in Brasília; Jucá et al [28] assessed the management of MSW in Recife through sustainability indicators across social, environmental, economic, and institutional dimensions; Fuss et al [29] analyzed the development of a framework to evaluate MSW in Belo Horizonte, integrating economic, environmental, and social dimensions; Miranda et al [30] studied the integration of recycling cooperatives in a medium-sized municipality (Londrina), aiming to assess their contributions within a circular economy structure and identify benchmarking options for similar cooperatives; and Alfaia et al [17] and Lino et al [22] carried out comprehensive reviews of MSW in Brazil. Other topics less explored in the literature include the management of specific types of waste, such as e-waste [31,32] and construction and demolition waste [33], waste characterization in Brazil [34], the impacts of the COVID-19 pandemic on solid waste generation in the country [35], public perceptions, residents' awareness and attitudes toward waste management practices in specific Brazilian cities [36], and bibliometric studies on the impact of PNRS on Brazilian scientific production [37].…”
Section: Introductionmentioning
confidence: 99%